COVID-19, Food Insecurity and a Government Response: Reflections from South Africa - Mlambo, Victor H.; Khuzwayo, Nonoxlo Nomfundo (Technium Social Sciences Journal, 2021)
The goal of this paper is to examine how life, already hard before the arrival of the COVID-19 pandemic has further deteriorated and compounded the ability of South Africans to access food. Departing, this paper argues that while food insecurity has always been a feature in South Africa, however, COVID-19 has laid bare the ineffective policy response by successive governments over the years. Food insecurity in the country not new, however, the government’s ineffective response allowed COVID-19 to intensify poverty and inequality among the most vulnerable. To explore how COVID-19 exacerbated the food insecurity problem in the country, this paper employed a qualitative research approach where secondary data was collected through a review of the literature. From the onset, it became observable that government responses to COVID-19 were not only going to cost jobs and further entrench poverty and inequality, but they were also going to exacerbate the food insecurity problem in the country. Even though government measures to cushion the poor and vulnerable were largely welcomed, they were tainted by corruption, thus clouding their overall effectiveness. It was recommended that the government ought to be proactive rather than reactive in addressing issues around food insecurity